A Bilayer Plasmonic Metasurface for Polarization‐Insensitive Bidirectional Perfect Absorption. Issue 2 (13th January 2020) - Li, Zhancheng; Liu, Wenwei; Tang, Chengchun; Cheng, Hua; Li, Zhi; Zhang, Yuebian; Li, Junjie; Chen, Shuqi; Tian, Jianguo
Abstract: The implementation of perfect absorption of optical waves in artificial nanostructures has attracted tremendous attention among the scientific community. Traditional approaches based on metamaterials can only absorb optical waves in one direction while reflecting optical waves in the other direction. Here, a polarization‐insensitive bidirectional perfect absorber that is composed of bilayer gold nano disks embedded into a silicon nitride substrate is demonstrated. The bidirectional perfect absorption in the proposed bilayer metasurface, which is irrelevant to the coherent of optical waves, is attributed to the multiple reflections and interference of optical waves in the bilayer structures. The proposed perfect absorber shall boost its applications in optical anti‐counterfeiting, integrated photodetectors, and solar thermal applications. Abstract : A bilayer plasmonic metasurface is utilized to realize polarization‐insensitive bidirectional perfect absorption of optical waves. With the advantages of having a polarization‐insensitive and bidirectional optical response, being alignment‐free, and irrelevant to the coherence of optical waves, the proposed bilayer metasurface shall boost its applications in optical anti‐counterfeiting, integrated photodetectors and solar thermal applications.